Can you put your finger on it? The effects of writing modality on Finnish students' recollection. Issue 2 (3rd July 2018) - Frangou, Satu-Maarit; Ruokamo, Heli; Parviainen, Tiina; Wikgren, Jan
ABSTRACT: Digitalisation has changed and broadened the ways people write. In higher education, typing is a common practice both for note-taking and for completing written assignments, relegating pen and paper to the last millennium. The cognitive and educational implications of this change, however, require further investigation. We assessed how three different methods of writing short stories affect students' subsequent memory retrieval. In a within-subjects design, Finnish students ( n  = 31) from the University of Lapland transcribed dictated stories using a pencil, a computer keyboard and a virtual touchscreen keyboard. The degree of recollection for each writing task was analysed 30 min after the session and then one week later. The main result is that handwriting led to significantly better recollection after both time delays. This corroborates and extends the findings reported in previous studies, and it calls for further research on writing methods and long-term memory. Additionally, as writing modality seems to affect recollection, reconsideration of instruction practices in higher education is suggested. Typing is the students' main method of writing and better typing competence can yield multiple benefits for them, including facilitating their academic work and enhancing the recollection of their own work.